Natural Disasters and Secondary School Performance: Evidence from the Coastal-Ecuadorian Earthquake - Garcés Padilla, Valeria Anabel (2021)
An empirical difference-in-difference strategy with matching is used to determine the impact of the 2016 Ecuadorian earthquake on the unemployment of high school graduates from the coastal region. Schools with similar sociodemographic characteristics were linked through propensity score matching to guarantee the assumption of parallel trends required within this context. After the shock, the effect is distinguished by year and differs according to the source of financing of the schools. The standardized scores of the nationally implemented high school exit exam (Ser Bachelor) were used to quantify the effect on student performance, as well as registered absenteeism. Due to the redistribution of students in schools, their performance worsened in private and coeducational schools after the earthquake, however, students in public schools slightly improved their average scores. The education level of parents is a key determinant in the demographic composition of schools after the earthquake. Absenteeism remains negligible, while standardized scores drop significantly in private and coeducational schools after 2016.